Determining the Relationship between the Performance of Investment Managers with their Decision in Investment Companies of Tehran Stock Exchange - Amir Reza Abbasi; Mohsen Nazem Bokaei; Naser Yazdani (مطالعات مدیریت راهبردی, 2017)
Examine the decision-making process can improve the quality of decision-making and better solve the problem. The decision to choose the correct option investment is considered to be one of the major decisions of individuals and companies. One of the factors that affect the behavior of investors, their decision-making style. In this study, the style Sproles and Kendall's decision to study the style of management decision making when investing and buying stocks is used. Which focuses on the attitudes of decision makers? Decision Style Inventory (CSI) company investment managers who have responsibilities ranged from 89 to 92, have been distributed. One-sample t- test was used for management decision making styles. Five style eight style of the model were identified among managers. To investigate the relationship between decision-making and investment performance managers the Pearson correlation test was used. Significant correlation coefficient r was used to confirm the test. The ideal style Whether or sensitivity to the quality, brand-sensitive companies listed on the stock exchange, sensitivity to price and exchange value and style habit and loyalty to a brand, were approved by the performance of investment managers and is significant.